Aerobic Allylation of Alcohols with Non-Activated Alkenes Enabled by Light-Driven Selenium-π-Acid Catalysis - Rode, Katharina; Palomba, Martina; Ortgies, Stefan; Rieger, Rene; Breder, Alexander (Synthesis, 2018)
A new organocatalytic protocol for the aerobic dehydrogenative allylation of alcohols using non-activated alkenes as the allylating reagent and ambient air as the terminal oxidant is established. Mechanistically, the procedure relies on the interplay of a diselane and a photoredox catalyst by means of a light-induced electron transfer process. Under optimized conditions, a broad range of both cyclic and acyclic ethers is accessed with very high functional group tolerance and excellent regioselectivity.
Keywords: alcohols; allylations; alkenes; oxidations; photoredox catalysis; selenium-π-acids